COOPERATION BETWEEN THE PUBLIC PROSECUTOR AND THE POLICE IN SERBIA - Soković, Snežana M; Čvorović, Dragana S; Turanjanin, Veljko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Contemporary trends in criminal procedure legislation are deliberately looking for efficiency as well as the instruments of implementation of international standards both in its quantitative and qualitative aspects. Doctrinal considerations find their footing in the decades-long reform of criminal procedural legislation of the Serbia, whereas the question that has always represented one of the most significant characteristics of criminal procedural legislation in general is the correlation between the public prosecutor and the police and its contribution to the efficiency of criminal proceedings. Serbia adopted new Criminal Procedure Code in 2011, which entered into the force during the 2013. According to the abovementioned, the authors pay special attention to the following issues: first, the notion of the police and the police functions; secondly, the correlation of the public prosecutor and the police as a factor in the efficiency of criminal proceedings; thirdly, empirical research and proposals de lege ferenda.